Cathodoluminescence microscopy and spectroscopy of forsterite from Kaba meteorite: An application to the study of hydrothermal alteration of parent body. (6th December 2013) - Gucsik, Arnold; Endo, Taro; Nishido, Hirotsugu; Ninagawa, Kiyotaka; Kayama, Masahiro; Bérczi, Szaniszló; Nagy, Szabolcs; Ábrahám, Péter; Kimura, Yuki; Miura, Hitoshi; Gyollai, Ildikó; Simonia, Irakli; et al.
Abstract Highly forsteritic olivine (Fo: 99.2–99.7) in the Kaba meteorite emits bright cathodoluminescence (CL). CL spectra of red luminescent forsterite grains have two broad emission bands at approximately 630 nm (impurity center of divalent Mn ions) in the red region and above 700 nm (trivalent Cr ions) in the red–IR region. The cores of the grains show CL blue luminescence giving a characteristic broad band emission at 400 nm, also associated with minor red emissions related to Mn and Cr ions. CL color variation of Kaba forsterite is attributed to structural defects. Electron probe microanalyzer (EPMA) analysis shows concentrations of Ca, Al, and Ti in the center of the forsterite grain. The migration of diffusible ions of Mn, Cr, and Fe to the rim of the Kaba meteoritic forsterite was controlled by the hydrothermal alteration at relatively low temperature (estimated at about 250 °C), while Ca and Al ions might still lie in the core. A very unusual phase of FeO (wüstite) was also observed, which may be a terrestrial alteration product of FeNi‐metal.